Pembuatan lembar kerja peserta didik berbasis accelerated learning pada materi usaha, pesawat sederhana, struktur dan fungsi tumbuhan untuk peserta didik SMP kelas VIII - mentari yashinta yashinta; Festiyed Festiyed; Murtiani Murtiani (Universitas Negeri Padang, 2019)
The use of LKPD in schools has not made students active in learning. This is because LKPD is less attractive and does not yet contain steps for activities. The effort to make students interested and active in learning is by using Accelerated Learning based LKPD. This study aims to produce Accelerated Learning based LKPD on business materials, simple planes, structure and plant functions for valid VIII grade junior high school students. This research focuses on the research of making teaching materials in the form of LKPD in line with Accelerated Learning in accordance with the steps of making teaching materials in the form of LKPD according to the Ministry of National Education. The results of the study are LKPD fulfilling very valid criteria. Based on the research that has been done, two research results are obtained. First, this research resulted in an accelerated learning worksheet for students. And the results of the second study are the results of the validity test conducted twice, with an average value of the first validity of 83 with very valid criteria and the average value of the second validity of 87 with very valid criteria. So, the conclusion of this research is that the worksheet for accelerated learning-based students is very feasible to be used in learning on work material, simple aircraft, structure and function of plant tissue.